ਡੇਅਰੀ ਦਾ ਹਿਸਾਬ ਕਿਤਾਬ ਰੱਖਣ ਲਈ ਵਹੀ ਖਾਤਾ - (:unkn) unknown (Punjab Agricultural University Ludhiana Punjab, 1993)
In this, how the business of dairy farm can be run well and how to keep its accounts, it has been told. record book for dairy business
Record Book for Dairy Business
Keywords: Punjabi; ਡੇਅਰੀ ਦਾ ਹਿਸਾਬ ਕਿਤਾਬ ਰੱਖਣ ਲਈ ਵਹੀ ਖਾਤਾ; Record Book for Dairy Business; Dairy Farming; Punjabi; Punjabi